2021
DOI: 10.1038/s41598-021-84417-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral functional networks during sleep in young and older individuals

Abstract: Even though sleep modification is a hallmark of the aging process, age-related changes in functional connectivity using functional Magnetic Resonance Imaging (fMRI) during sleep, remain unknown. Here, we combined electroencephalography and fMRI to examine functional connectivity differences between wakefulness and light sleep stages (N1 and N2 stages) in 16 young (23.1 ± 3.3y; 7 women), and 14 older individuals (59.6 ± 5.7y; 8 women). Results revealed extended, distributed (inter-between) and local (intra-with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…The findings reported are not expected to be driven by arousal differences between young and old subjects. Indeed, a recent study (Daneault et al, 2021) has found no statistically significant differences in FC between young and old people and no interaction with age when comparing wakefulness and N1 during 100 minutes of eye‐closed acquisition. It is of note that the subjects employed in our study were asked to keep their eyes‐open for the entire duration of the acquisition and this should prevent N1 stage (Gu, Han, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The findings reported are not expected to be driven by arousal differences between young and old subjects. Indeed, a recent study (Daneault et al, 2021) has found no statistically significant differences in FC between young and old people and no interaction with age when comparing wakefulness and N1 during 100 minutes of eye‐closed acquisition. It is of note that the subjects employed in our study were asked to keep their eyes‐open for the entire duration of the acquisition and this should prevent N1 stage (Gu, Han, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…It is of note that the subjects employed in our study were asked to keep their eyes‐open for the entire duration of the acquisition and this should prevent N1 stage (Gu, Han, & Liu, 2019). However, even if we assume that some of them fell into a N1 sleep stage, it does not foresee significant differences in FC between young and old, based on (Daneault et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, direct stimulation of individual thalamic nuclei has been shown to drive arousal state transitions 24,[30][31][32][33][34][35][36][37][38][39][40][41][42] . Human imaging studies have further confirmed that spontaneous thalamic activity shifts across arousal state: functional magnetic resonance imaging (fMRI) studies have shown altered thalamocortical and intrathalamic connectivity during sleep [43][44][45][46] , and distinct spatiotemporal dynamics linked to arousal state fluctuations [47][48][49] . Intriguingly, the thalamus has also been shown to activate during arousal state transitions in humans 50,51 .…”
mentioning
confidence: 94%
“…Finding distinguishing features of the human brain mechanisms considering different states of mind seems to be a reliable approach toward unraveling the neural correlate of consciousness. In fact, several studies using neuroimaging data have shown consistent correlations between mental states and functional brain networks in humans [1][2][3][4][5][6][7]. Emergent behaviors on networked systems are determined by their topological structure.…”
Section: Introductionmentioning
confidence: 99%